PEMANFAATAN KEANEKARAGAMAN HAYATI LOKAL KERINCI SEBAGAI SUMBER PEMBELAJARAN BIOLOGI DI SEKOLAH - Dede Ameliya (IICLS (Indonesian Institute for Corporate Learning and Studies), 2023)
Biodiversity is a crucial aspect of nature that must be studied and preserved. This research aims to explore the utilization of local biodiversity in Kerinci as a source for biology education in schools. Employing a qualitative approach, data were collected through interviews, observations, and documentation from several schools in the Kerinci region. The results indicate that integrating local biodiversity elements into biology teaching significantly enhances students’ interest and understanding of the subject matter. Specifically, the findings show that when students learn about local flora and fauna, they become more engaged and motivated, resulting in improved academic performance. The study underscores the importance of contextualizing learning materials to reflect the students' immediate environment, making the learning experience more relevant and relatable. Furthermore, it suggests that teachers should incorporate local biological resources in their curriculum to enrich students' educational experiences and foster a deeper appreciation for their natural surroundings. The research is expected to contribute positively to the development of a more relevant and contextual biology curriculum that aligns with the students' cultural and environmental contexts. By highlighting the significance of local biodiversity in education, this study advocates for a curriculum that not only enhances scientific understanding but also promotes environmental awareness and conservation efforts among students.